Stop Negative Thinking Effects for Drug Dependence - Sri Endang Windiarti; Indriati Indriati; Fajar Surachmi (Poltekkes Kemenkes Semarang, 2013)
The purpose of this study was to determine the effect of therapy stop thinking negatively against drug addiction in Rehabilitation Orphanage Rumah Damai Gunung Pati Semarang. This research is quasy experiment with pretest - posttes without the control group design. Thirty respondents were taken to the reseach sujects. Stop thinking negative therapy before and after thebehavior of drug addiction there are differences (t = 0.00), so it can be stated that the therapy stop thinking negatively influence behavior ependence. This study can be resumed with another therapeutic model, in order to improve government programs, communities and families to reduce drug dependency problems.